Zirconium alloy hot extrusion gradient lubricating coating material and use method thereof

By using zirconium alloy hot extrusion gradient lubrication coating materials and using a combination of lubricating coatings and anti-oxidation coatings, the problems of discontinuous lubrication and high friction coefficient of zirconium alloys in the hot extrusion process have been achieved, achieving high temperature retention. Good lubrication properties and the effect of extending the heat preservation time.

CN119350892APending Publication Date: 2025-01-24XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411337898.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the hot extrusion process, zirconium alloys are easily contaminated by elements such as oxygen, nitrogen, and hydrogen. They have high deformation resistance and poor fluidity, resulting in discontinuous lubrication and high friction coefficient, making it difficult to maintain good lubrication performance at high temperatures.

Method used

Using a tadpole alloy heat squeezed gradient material composed of lubricating coatings and antioxidant coatings, the lubricating coatings consist of MOS2@SiO2 composite material, phosphate aluminum, graphite and tungsten sulfide. Composition of sodium silicate and low soft dotted glass powder to form coatings with excellent lubrication performance and antioxidant capacity by regulating the proportion of each component and curing process of each component.

Benefits of technology

Maintain excellent lubrication performance at 760 ° C, extend the heat preservation time before processing, reduce the friction coefficient, improve the stability and uniformity of the coating, and avoid the oxidation failure of the lubricating ingredient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350892A_ABST
    Figure CN119350892A_ABST
Patent Text Reader

Abstract

The invention discloses a zirconium alloy hot extrusion gradient lubricating coating material and a use method thereof. The coating material is composed of a lubricating coating and an anti-oxidation coating. The lubricating coating is prepared from the following raw materials in parts by weight: 10 to 22 parts of MoS2atSiO2 composite material, 6 to 12 parts of aluminum dihydrogen phosphate, 6 to 12 parts of graphite, 2 to 8 parts of tungsten disulfide and 46 to 76 parts of deionized water. The anti-oxidation coating is prepared from the following raw materials in parts by weight: 12-18 parts of instant powdery sodium silicate, 30-35 parts of low-melting-point glass powder and 47-58 parts of deionized water. The zirconium alloy hot extrusion gradient lubricating coating provided by the invention can have excellent lubricating performance at the highest temperature of 760 DEG C, and can prolong the heat preservation time of a workpiece before processing. The method can well solve the problems that the zirconium alloy workpiece is uneven in temperature and difficult to process smoothly due to the fact that the use effect of the lubricating coating is usually considered and long-time heat preservation cannot be achieved in actual production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating materials, and in particular relates to a zirconium alloy hot extrusion gradient lubricating coating material and a use method thereof. Background Art

[0002] Nuclear power is recognized as a clean energy source in the world, with the characteristics of high efficiency, safety and economy. Zirconium alloy has become an indispensable material in nuclear reactors due to its excellent corrosion resistance, small thermal neutron absorption cross section and good compatibility with uranium fuel. However, zirconium alloy is easily contaminated by oxygen, nitrogen, hydrogen and other elements during hot extrusion process, has high deformation resistance, poor fluidity, easy adhesion to molds and other problems, which puts forward higher requirements on the lubrication process during processing.

[0003] Usually, zirconium alloys are lubricated by soft metal coating or glass lubricant in actual production. However, the use of soft metal coating such as copper can easily cause discontinuity of lubrication, and the copper skin needs to be pickled off after extrusion, which is a complicated process; and the high-temperature viscosity fluctuation range of glass lubricants is large, and glass powder is prone to fall off and irregular flow during hot extrusion, resulting in lubrication failure. Another part will use solid lubricating coatings to assist in extrusion production, but there are currently few studies in China on solid lubricating coatings suitable for high temperatures of 680℃-780℃. The Chinese patent application (CN 110157521 A) discloses a material for hot extrusion lubrication and thermal protection of zirconium alloys. At 750℃, the friction factor measured by the ring compression method is approximately 0.2, and the friction coefficient is relatively high. In addition, in actual production, the zirconium alloy billet needs to be heated to the processing temperature and kept warm for a period of time after the lubricating coating is applied before it can be sent to the extrusion barrel. Therefore, higher requirements are placed on the coating to maintain good lubrication performance in a high temperature environment for a long time. Therefore, it is extremely necessary to study a lubricating coating suitable for long insulation time at high temperature. Summary of the invention

[0004] The first object of the present invention is to provide a zirconium alloy hot extrusion gradient lubricating coating material, and the second object of the present invention is to provide a method for using the lubricating coating material.

[0005] The first object of the present invention is achieved by providing a zirconium alloy hot extrusion gradient lubricating coating material, which is composed of a lubricating coating and an anti-oxidation coating; The lubricating coating is composed of the following raw materials in parts by weight: MoS 2 @SiO 2 10-22 parts of composite material, 6-12 parts of aluminum dihydrogen phosphate, 6-12 parts of graphite, 2-8 parts of tungsten disulfide, and 46-76 parts of deionized water; The anti-oxidation coating is composed of the following raw materials in parts by weight: 12-18 parts of instant powdered sodium silicate, 30-35 parts of low softening point glass powder, and 47-58 parts of deionized water.

[0006] The second object of the present invention is achieved in this way. The method for using the zirconium alloy hot extrusion gradient lubricating coating material is specifically to fully immerse the zirconium alloy in the lubricating coating for 5-10 seconds, then take it out, let it stand at room temperature for 5-10 minutes, and then transfer it into a 200-220°C oven for heating and curing for 20-30 minutes. After cooling, fully immerse it in the material of the anti-oxidation layer for 5-10 seconds, then take it out, let it stand at room temperature for 5-10 minutes, and then transfer it into an oven for two heating and curing to obtain a gradient lubricating coating.

[0007] The present invention adjusts the ratio of molybdenum disulfide, graphite, tungsten disulfide and binder in the lubricating coating to make the coating have excellent lubrication performance, and uses a curing process to ensure the bonding strength between the coating and the workpiece and to make it easy to remove from the workpiece after extrusion. 2 The outer shell forms an oxygen barrier to prevent the lubricating phase from oxidizing and failing when in contact with air at high temperatures, thus achieving excellent lubrication performance at high temperatures. By adjusting the ratio of glass powder to sodium silicate in the anti-oxidation coating, the coating can remain stable under long-term heat preservation. The longer the heat preservation time, the more uniform and dense the coating is, preventing the lubricating components and workpieces from being oxidized.

[0008] The zirconium alloy hot extrusion gradient lubricating coating provided by the present invention can have excellent lubricating performance at a maximum temperature of 760°C and can prolong the heat preservation time of the workpiece before processing. The present invention can well solve the problem that in actual production, the use effect of the lubricating coating is usually considered, but the heat preservation cannot be carried out for a long time, resulting in uneven temperature of the zirconium alloy workpiece and difficulty in smooth processing. The coating of the present invention is not easy to volatilize, has no chemical pollution, is non-toxic, and the coating will peel off as the workpiece cools after extrusion is completed ( Figure 4 ), which is convenient for cleaning after processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is a scanning electron microscope image of a cross section of the coating prepared in Example 1; Figure 2 This is a macroscopic image of the coating of Example 1 of the present invention; Figure 3 This is a scanning electron microscope image of the coating prepared in Example 2; Figure 4 This is a picture of the coating peeling off after cooling down in Example 1 of the present invention; Figure 5 The friction coefficient curve of the coating prepared in Example 1 at 700° C. and 760° C. for 10 minutes respectively; Figure 6 The friction coefficient curve of the coating prepared in Example 1 at 700° C. and 760° C. for 30 minutes respectively; Figure 7The friction coefficient curve of the coating prepared in Example 1 at 700° C. and 760° C. for 60 min respectively; Figure 8 The friction coefficient curve of the commercially available lubricating material of Comparative Example 1 at 700°C for 10 minutes and 30 minutes; Fig. 9 The friction coefficient curve of the coating of comparative example 2 kept at 700°C for 10 minutes and 30 minutes. DETAILED DESCRIPTION

[0010] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited in any way. Any changes or substitutions made based on the teachings of the present invention belong to the protection scope of the present invention.

[0011] The invention discloses a zirconium alloy hot extrusion gradient lubricating coating material, which is composed of a lubricating coating and an anti-oxidation coating; The lubricating coating is composed of the following raw materials in parts by weight: MoS 2 @SiO 2 10-22 parts of composite material, 6-12 parts of aluminum dihydrogen phosphate, 6-12 parts of graphite, 2-8 parts of tungsten disulfide, and 46-76 parts of deionized water; The anti-oxidation coating is composed of the following raw materials in parts by weight: 12-18 parts of instant powdered sodium silicate, 30-35 parts of low softening point glass powder, and 47-58 parts of deionized water.

[0012] The MoS 2 @SiO 2 The preparation method of the composite material is as follows: 1) Sodium molybdate, thioacetamide and cetyl trimethyl ammonium bromide in a mass ratio of 16:18:1-16:21:1 are added to deionized water, fully ultrasonically dispersed, stirred evenly, and then transferred to a reactor, heated to 210-220°C at a heating rate of 10°C per minute and kept warm for 24-30 hours, cooled with the furnace and centrifuged, the precipitate is collected, washed and dried to obtain MoS with a particle size of 300-400 nanometers. 2 ball; 2) The MoS obtained in step 1) 2 The spheres were dispersed in an ethanol solution with a volume fraction of 85% at a mass ratio of 1:32-1:40, and then ethyl orthosilicate and ammonia water were added, with a volume ratio of ethyl orthosilicate to the dispersed solution of 1:20-1:25. The mixture was stirred at a speed of 420-450 r / min for 24-30 hours. After completion, the precipitate was collected by centrifugation at a speed of 5000-6000 rpm for 15-20 minutes, washed and dried to obtain MoS 2 @SiO 2 Composite materials.

[0013] In step 1), the ultrasonic dispersion power is 300-400W, and the ultrasonic time is 1-4h; In step 2), the volume ratio of ethyl orthosilicate to ammonia water is 2:1-3:2.

[0014] The glass powder comprises, by mass fraction, 31-29 parts of lead dioxide, 14-12 parts of silicon dioxide, 3-2 parts of aluminum oxide, and 1-0.5 parts of boron oxide.

[0015] The volume ratio of ethyl orthosilicate and ammonia water is 2:1-3:2.

[0016] The preparation method of the lubricating coating is as follows: MoS 2 @SiO 2 The composite material, aluminum dihydrogen phosphate, graphite, tungsten disulfide and deionized water are mixed and then ultrasonically stirred to obtain the composite material. The ultrasonic power is 300W-400W, the stirring speed is 700-750r / min, and the stirring time is 1-2 hours.

[0017] The preparation method of the anti-oxidation coating is as follows: Add instant powdered sodium silicate into deionized water, and stir continuously for 2-3 hours at 450-600 r / min under 35-45°C environment; add low softening point glass powder, raise the temperature to 50-55°C, and stir continuously for 2-3 hours at 600-650 r / min to obtain the material of the antioxidant layer.

[0018] The present invention also provides a method for using the zirconium alloy hot extrusion gradient lubricating coating material, specifically, the zirconium alloy is fully immersed in the lubricating coating for 5-10 seconds, then taken out, allowed to stand at room temperature for 5-10 minutes, and then transferred into a 200-220°C oven for heating and curing for 20-30 minutes, and after cooling, it is fully immersed in the material of the anti-oxidation layer for 5-10 seconds, then taken out, allowed to stand at room temperature for 5-10 minutes, and then transferred into an oven for heating and curing twice to obtain a gradient lubricating coating.

[0019] The two-step curing method is as follows: first, heat up to 80-85°C at a rate of 10-12°C per minute and keep warm for 10-15 minutes, then heat up to 200-210°C at a rate of 10-15°C per minute and keep warm for 20-30 minutes Example 1 1. MoS 2 @SiO 2Preparation of composite materials: 1) Sodium molybdate, thioacetamide and cetyl trimethyl ammonium bromide in a mass ratio of 16:18:1 were added to deionized water, fully ultrasonically dispersed, stirred evenly, and then transferred to a reactor, heated to 210°C at a heating rate of 10°C per minute and kept warm for 24 hours, cooled in the furnace and centrifuged, the precipitate was collected, washed and dried to obtain MoS with a particle size of 300-400 nm. 2 ball; 2) Take 8 portions of MoS obtained in step 1) 2 The balls were added to an 85% ethanol solution and ultrasonically dispersed at a power of 300-400 W for 4 h. TEOS and ammonia water were added in a volume ratio of 3:2 and stirred at 450 r / min for 24 h. After completion, the precipitate was collected by centrifugation at 6000 rpm for 15 min, washed and dried to obtain MoS 2 @SiO 2 Composite materials. MoS 2 The mass ratio of the ball to the ethanol solution is 1:32, and the volume ratio of the ethanol solution to tetraethyl orthosilicate is 20:1.

[0020] 2. By mass fraction, 10 parts of MoS 2 @SiO 2 The composite material, 6 parts of aluminum dihydrogen phosphate, 12 parts of graphite, 8 parts of tungsten disulfide and 76 parts of deionized water were ultrasonically oscillated and continuously stirred at a speed of 700 r / min for 1 hour to obtain an effective lubricating coating.

[0021] 3. By mass fraction, 18 parts of instant powdered sodium silicate were added to 47 parts of deionized water, and the mixture was stirred at 450 r / min for 2 hours at 35°C to obtain solution B; 4. Add 30 parts of low softening point glass powder to the above solution B, raise the temperature to 50°C, and stir at a speed of 600 r / min for 2 hours to obtain an antioxidant coating.

[0022] When using, fully immerse the zirconium alloy extruded rod in the lubricating coating for 5-10 seconds, take it out and place it vertically at room temperature to allow the coating to quickly and evenly level and cover the surface of the rod, so that the coating thickness is uniform. Then place the test piece in an oven and heat it to 200°C at a rate of 2°C per minute. Let it stand at 200°C for 20 minutes to transform the aluminum dihydrogen phosphate into a reinforced structure, thereby improving the bonding strength between the lubricating layer and the substrate; After the above operation, the rod was taken out and allowed to stand for 10 minutes to cool down, then the rod was slowly immersed in the anti-oxidation coating for 5-10 seconds, and then allowed to stand at room temperature for 5 minutes to allow the coating to evenly cover the surface of the specimen. The specimen was then heated to 80°C at a rate of 10°C per minute for 10 minutes, and then heated to 200°C at a rate of 10°C per minute for 20 minutes. The lubricating layer and the anti-oxidation layer diffused with each other to form a gradient structure coating, such as Figure 1 shown.

[0023] Figure 4 This is a peeling diagram of the coating after cooling in Example 1. Due to the changes in thermal expansion coefficient, lattice strain and Young's modulus caused by the surface effect when the coating and zirconium alloy substrate of the present invention are cooled after heating, the thermal strain causes the coating to automatically fall off, and the shedding ability increases with the increase of processing temperature, which is beneficial to the surface cleaning and treatment after the zirconium alloy processing in the later stage, and simplifies the process steps.

[0024] Example 2 1. By mass fraction, 22 parts of MoS 2 @SiO 2 The composite material, 12 parts of aluminum dihydrogen phosphate, 6 parts of graphite, 2 parts of tungsten disulfide and 46 parts of deionized water were subjected to ultrasonic oscillation and continuously stirred at a speed of 700 r / min for 1 hour to obtain an effective lubricating coating.

[0025] 2. By mass fraction, 12 parts of instant powdered sodium silicate were added to 58 parts of deionized water, and stirred at 450 r / min for 2 hours at 35°C to obtain solution B; 3. Add 35 parts of low softening point glass powder to the above solution B, raise the temperature to 50°C, and stir at a speed of 600 r / min for 2 hours to obtain an antioxidant coating.

[0026] When using, fully immerse the zirconium alloy extruded rod in the lubricating coating for 5-10 seconds, take it out and place it vertically at room temperature to allow the coating to quickly and evenly level and cover the surface of the specimen, so that the coating thickness is uniform. Then place the specimen in an oven and heat it to 200°C at a rate of 2°C per minute. Let it stand at 200°C for 20 minutes to transform the aluminum dihydrogen phosphate into a reinforced structure, thereby increasing the bonding strength between the lubricating layer and the substrate. After the above operation, the rod was taken out and left to cool for 10 minutes, then the rod was slowly immersed in the anti-oxidation coating for 5-10 seconds, and then left to stand at room temperature for 5 minutes to allow the coating to evenly cover the surface of the specimen. The specimen was then heated to 80°C at a rate of 10°C per minute for 10 minutes, and then heated to 200°C at a rate of 10°C per minute for 20 minutes. The lubricating layer and the anti-oxidation layer diffused with each other to form a gradient structure, such as Figure 2-3 shown.

[0027] Example 3 1. MoS 2 @SiO 2 Preparation of composite materials: 1) Sodium molybdate, thioacetamide and cetyl trimethyl ammonium bromide in a mass ratio of 16:21:1 were added to deionized water, fully ultrasonically dispersed, stirred evenly, and then transferred to a reactor, heated to 220°C at a heating rate of 10°C per minute and kept warm for 24 hours, cooled in the furnace and centrifuged, the precipitate was collected, washed and dried to obtain MoS with a particle size of 300-400 nm. 2 ball; 2) Take 5 portions of MoS obtained in step 1) 2 The balls were added to 85% ethanol solution, ultrasonically dispersed at 400 W for 2 h, and ethyl orthosilicate and ammonia water were added in a volume ratio of 2:1. The mixture was stirred at 420 r / min for 30 h. After completion, the precipitate was collected by centrifugation at 5000 rpm for 20 min, washed and dried to obtain MoS 2 @SiO 2 Composite materials. Among them, MoS 2 The mass ratio of the ball to the ethanol solution is 1:40, and the volume ratio of the ethanol solution to tetraethyl orthosilicate is 1:25.

[0028] 2. By mass fraction, 16 parts of MoS 2 @SiO 2 The composite material, 9 parts of aluminum dihydrogen phosphate, 9 parts of graphite, 5 parts of tungsten disulfide and 50 parts of deionized water were ultrasonically oscillated and continuously stirred at a speed of 750 r / min for 2 hours to obtain an effective lubricating coating.

[0029] 3. By mass fraction, 15 parts of instant powdered sodium silicate were added to 52 parts of deionized water, and the mixture was stirred at 600 r / min for 2 hours at 45°C to obtain solution B; 4. Add 32 parts of low softening point glass powder to the above solution B, raise the temperature to 55°C, and stir at a speed of 600 r / min for 2 hours to obtain an antioxidant coating.

[0030] When using, fully immerse the zirconium alloy extruded rod in the lubricating coating for 5-10 seconds, take it out and place it vertically at room temperature to allow the coating to quickly and evenly level and cover the surface of the rod, so that the coating thickness is uniform. Then place the test piece in an oven and heat it to 200°C at a rate of 2°C per minute. Let it stand at 220°C for 30 minutes to transform the aluminum dihydrogen phosphate into a reinforced structure, thereby improving the bonding strength between the lubricating layer and the substrate; After the above operation, the rod was taken out and allowed to cool, then slowly immersed in the anti-oxidation coating for 5-10 seconds, and then allowed to stand at room temperature for 10 minutes to allow the coating to evenly cover the surface of the specimen. The specimen was then heated to 85°C at a rate of 15°C per minute for 15 minutes, and then heated to 210°C at a rate of 15°C per minute for 30 minutes, so that the lubricating layer and the anti-oxidation layer diffused with each other to form a gradient structure lubricating coating.

[0031] Comparative Example 1 Take a certain amount of the currently imported zirconium alloy hot press processing special lubricant M on the market, calculated by mass, mix 1 part of M with 2 parts of deionized water, perform ultrasonic oscillation and continuously stir at a speed of 700r / min for 1 hour to obtain a lubricating coating.

[0032] When using, fully immerse the zirconium alloy extruded rod in the lubricating coating for 5-10 seconds, take it out and place it vertically at room temperature to allow the coating to evenly flow and cover the surface of the specimen. Then place the specimen in an oven and heat it to 200°C at a rate of 2°C per minute, and let it stand for 20 minutes to complete the curing to obtain the lubricating coating.

[0033] Comparative Example 2 In this comparative example, the lubricating material used is the same as that in Example 1, except for the preparation method of the lubricating coating.

[0034] The preparation method of the lubricating coating of comparative example 2 is as follows: 1. Fully immerse the zirconium alloy extruded rod in the lubricating coating prepared in Example 1 for 5-10 seconds, take it out and place it vertically at room temperature to allow the coating to quickly and evenly level and cover the surface of the test piece, so that the coating thickness is uniform. Then place the test piece in an oven and heat it to 200°C at a rate of 2°C per minute. Let it stand at 200°C for 20 minutes to transform the aluminum dihydrogen phosphate into a reinforced structure, thereby improving the bonding strength between the lubricating layer and the substrate; 2. After the above operation is completed, take out the rod and let it stand for 10 minutes to cool down. Then slowly immerse the specimen in the anti-oxidation layer coating for 5-10 seconds. After taking it out, let it stand at room temperature for 15 minutes to allow the coating to evenly cover the surface of the specimen and solidify to obtain a lubricating coating.

[0035] Test Example 1 1. The tribological properties of the lubricating coating prepared in Example 1 were tested on a MFT-5000 (RTEC, USA) high temperature friction tester. The load was 10N, the rotation speed was 30r / min, the rotation radius was 15mm, and the corresponding linear speed was about 47mm / s. The dual ball was a silicon nitride ceramic ball (radius was 9.525mm). The friction test was carried out at 700°C and 760°C for 10min, 30min, and 60min, respectively. The friction link lasted for 180s, and the real-time friction coefficient was recorded. Each group of experiments was repeated more than three times. The experimental results are shown in FIG. Figure 5-7shown.

[0036] Result analysis: From Figure 5-7 It can be seen that within the holding time of 30 minutes, the friction coefficient of the lubricating coating of Example 1 is always lower than 0.2 and remains stable, and the lowest can reach 0.08. The lubricating coating of Example 1 also maintains excellent coating performance when kept at 760°C for 60 minutes, and the average friction coefficient is close to 0.1, which fully meets the processing requirements of zirconium alloy hot extrusion.

[0037] 2. The tribological performance of the lubricating coating prepared in Example 1-2 was tested in a MFT-5000 (RTEC, USA) high temperature friction tester. The load was 10N, the rotation speed was 30r / min, the rotation radius was 15mm, and the corresponding linear speed was about 47mm / s. The dual ball was a silicon nitride ceramic ball (radius was 9.525mm). The friction test was carried out at 700°C for 10min and 30min respectively. The friction link lasted for 180s, and the real-time friction coefficient was recorded. Each group of experiments was repeated more than three times. The experimental results are shown in the figure. Figure 8-9 shown.

[0038] Result analysis: From Figure 8 It can be seen that the friction coefficient of the lubricating coating in Comparative Example 1 is higher than 0.2, and the friction coefficient fluctuates greatly after long-term heat preservation, and the performance is unstable.

[0039] The average friction coefficient of the lubricating coating in Comparative Example 2 is about 0.2. Under the same experimental conditions, its tribological performance is worse than that of the coating obtained by two-step temperature curing in Example 1.

[0040] In summary, the lubricating coating prepared by the present invention has excellent and stable lubrication performance at 760° C., and can extend the heat preservation time of the workpiece before processing.

Claims

1. A zirconium alloy hot extrusion gradient lubricating coating material, characterized in that: The coating material consists of a lubricating coating and an anti-oxidation coating; The lubricating coating is composed of the following raw materials in parts by weight: 10-22 parts of MoS2@SiO2 composite material, 6-12 parts of aluminum dihydrogen phosphate, 6-12 parts of graphite, 2-8 parts of tungsten disulfide, and 46-76 parts of deionized water; The anti-oxidation coating is composed of the following raw materials in parts by weight: 12-18 parts of instant powdered sodium silicate, 30-35 parts of low softening point glass powder, and 47-58 parts of deionized water.

2. The zirconium alloy hot extrusion gradient lubricating coating material according to claim 1, characterized in that: The preparation method of the MoS2@SiO2 composite material is as follows: 1) Sodium molybdate, thioacetamide and cetyl trimethyl ammonium bromide in a mass ratio of 16:18:1-16:21:1 are added to deionized water, fully ultrasonically dispersed, stirred evenly, and then transferred to a reactor, heated to 210-220°C at a heating rate of 10°C per minute and kept warm for 24-30 hours, cooled with the furnace and centrifuged, the precipitate was collected, washed and dried to obtain MoS2 balls with a particle size of 300-400 nanometers; 2) The MoS2 spheres obtained in step 1) are dispersed in an ethanol solution with a volume fraction of 85% at a mass ratio of 1:32-1:40, and then tetraethyl orthosilicate and ammonia water are added, and the volume ratio of tetraethyl orthosilicate to the dispersed solution is 1:20-1:

25. Stirring is continued at a speed of 420-450 r / min for 24-30 hours. After completion, the precipitate is collected after centrifugation at a speed of 5000-6000 rpm for 15-20 minutes, washed and dried to obtain a MoS2@SiO2 composite material.

3. The zirconium alloy hot extrusion gradient lubricating coating material according to claim 2, characterized in that: In step 1), the ultrasonic dispersion power is 300-400W, and the ultrasonic time is 1-4h; In step 2), the volume ratio of ethyl orthosilicate to ammonia water is 2:1-3:

2.

4. The zirconium alloy hot extrusion gradient lubricating coating material according to claim 1, characterized in that: The glass powder comprises, by mass fraction, 31-29 parts of lead dioxide, 14-12 parts of silicon dioxide, 3-2 parts of aluminum oxide, and 1-0.5 parts of boron oxide.

5. The zirconium alloy hot extrusion gradient lubricating coating material according to claim 1, characterized in that: The preparation method of the lubricating coating is as follows: MoS2@SiO2 composite material, aluminum dihydrogen phosphate, graphite, tungsten disulfide and deionized water are mixed and then ultrasonically stirred to obtain the lubricating coating.

6. The zirconium alloy hot extrusion gradient lubricating coating material according to claim 5, characterized in that: The ultrasonic power is 300W-400W, the stirring speed is 700-750r / min, and the stirring time is 1-2 hours.

7. The zirconium alloy hot extrusion gradient lubricating coating material according to claim 1, characterized in that: The preparation method of the anti-oxidation coating is as follows: Add instant powdered sodium silicate into deionized water, and stir continuously for 2-3 hours at 450-600 r / min under 35-45°C environment; add low softening point glass powder, raise the temperature to 50-55°C, and stir continuously for 2-3 hours at 600-650 r / min to obtain the material of the antioxidant layer.

8. The method for using the zirconium alloy hot extrusion gradient lubricating coating material according to claim 1, characterized in that: The zirconium alloy is fully immersed in the material of the lubricating layer for 5-10 seconds, then taken out, allowed to stand at room temperature for 5-10 minutes, and then transferred into a 200-220°C oven for heating and curing for 20-30 minutes. After cooling, it is fully immersed in the material of the anti-oxidation layer for 5-10 seconds, then taken out, allowed to stand at room temperature for 5-10 minutes, and then transferred into an oven for two heating and curing to obtain a gradient lubricating coating.

9. The method for using the gradient structure zirconium alloy hot extrusion lubricating coating according to claim 8, characterized in that: The two-time temperature rise curing method is as follows: first, heat up to 80-85°C at a rate of 10-12°C per minute and keep warm for 10-15 minutes, then heat up to 200-210°C at a rate of 10-15°C per minute and keep warm for 20-30 minutes.

Citation Information

Patent Citations

  • Material for zirconium alloy hot extrusion lubrication and heat protection, preparation and application method

    CN110157521A